2017
DOI: 10.1097/itx.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of chronic ocular itch: a cross-sectional survey

Abstract: Introduction:In this cross-sectional study, we aimed to determine the prevalence and characteristics of chronic ocular itch in an outpatient ophthalmology and optometry clinic.Methods:Four hundred patients from an outpatient ophthalmology and optometry clinic were enrolled. The presence and characteristics of chronic ocular itch were assessed by a questionnaire. Data regarding ophthalmologic, dermatologic, and systemic conditions as well as current medications were extracted from medical records.Results:Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Notably, sensory descriptors applied by patients with DE resemble those applied by patients with painful peripheral neuropathies [1, 5, 6]. Many individuals with ocular conditions also report itch, sometimes occurring concurrent with pain [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Notably, sensory descriptors applied by patients with DE resemble those applied by patients with painful peripheral neuropathies [1, 5, 6]. Many individuals with ocular conditions also report itch, sometimes occurring concurrent with pain [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Many ophthalmologic conditions cause ocular pruritus, including allergic conjunctivitis, dry eye syndrome and blepharitis [ 2 ]. A study of 400 patients consulting an ophthalmology center in Philadelphia found a prevalence of chronic pruritus of 29.5%, with a majority of allergic conjunctivitis (51.8%), dry eye syndrome (40.1%) and blepharitis (43.8%) [ 3 ]. This study reported a higher prevalence of pruritus in women.…”
Section: Introductionmentioning
confidence: 99%
“…Although itch is considered the cardinal symptom of allergic conjunctivitis, ocular burning, stinging and even pain are other prominent complaints. In one study of individuals with chronic ocular itch, more than half of whom had underlying allergic conjunctivitis, itch was concurrent with pain in 25% of cases [2]. Ocular itch was also described as burning and tingling in half of the cases.…”
Section: Introductionmentioning
confidence: 99%